2019
DOI: 10.7717/peerj.7260
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes of medicinally importantTeucriumspecies and comparative analyses with related species from Lamiaceae

Abstract: Teucrium is one of the most economically and ecologically important genera in the Lamiaceae family; however, it is currently the least well understood at the plastome level. In the current study, we sequenced the complete chloroplast (cp) genomes of T. stocksianum subsp. stenophyllum R.A.King (TSS), T. stocksianum subsp. stocksianum Boiss. (TS) and T. mascatense Boiss. (TM) through next-generation sequencing and compared them with the cp genomes of related species in Lamiaceae (Ajuga reptans L., Caryopteris mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
4
9
0
Order By: Relevance
“…The study of different repeats (palindromic, forward, and tandem) in our sequenced cp genome showed variation in the number of repeats, which is similar to other species previously studied [ 59 ]. In all types of repeats, tandem repeats were found more than palindromic and forward repeats in four cp genomes; these results are consistent with previous reports of Teucrium and Commiphora species [ 60 , 61 ], as well as S. miltiorrhiza [ 62 ]. Similarly, simple sequence repeats (SSRs) usually have a higher rate of mutation compared with other neutral regions of DNA due to slipped strand mispairing.…”
Section: Discussionsupporting
confidence: 92%
“…The study of different repeats (palindromic, forward, and tandem) in our sequenced cp genome showed variation in the number of repeats, which is similar to other species previously studied [ 59 ]. In all types of repeats, tandem repeats were found more than palindromic and forward repeats in four cp genomes; these results are consistent with previous reports of Teucrium and Commiphora species [ 60 , 61 ], as well as S. miltiorrhiza [ 62 ]. Similarly, simple sequence repeats (SSRs) usually have a higher rate of mutation compared with other neutral regions of DNA due to slipped strand mispairing.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the same family (Acanthaceae), Ding, et al 42 and Huang, et al 44 previously reported the size of protein coding genes, rRNA, tRNA, number of genes, number of protein coding genes, number of rRNA and number of tRNA in A. paniculate and A. knappiae www.nature.com/scientificreports/ which is similar to what we found in the A. marina. Similarly, almost same results were observed in the recently reported chloroplast genomes of C. gileadensis 50 , Teucrium species 53 , Vachellia nilotica and Senegalia senegal 54 . In the chloroplast genome, microsatellites or SSRs distributed in the genome with the length of almost 1 bp to 6 bp.…”
Section: Discussionsupporting
confidence: 89%
“…The number of repeats, including forward, tandem, and palindromic repeats, were studied in the chloroplast genomes sequenced and compared, and were found in a larger amount than in the previously reported cp genome of V. fordii (49 repeats) [32]. Among these repeats, tandem repeats were found several times more than palindromic and forward repeats, which are consistent with the Teucrium and Commiphora species [30,31], as well as S. miltiorrhiza [39], as previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…All of them were assembled into a single chloroplast genome presenting a typical quadripartite structure. Analysis of two sequenced Euphorbia genomes revealed that, like most of the higher angiosperm genomes, they comprised the tetrahedral structure containing two pairs of inverted repeats, one large single-copy region and one small single-copy region [4,31]. There was a 186 bp difference observed between the two sequenced chloroplast genomes, and the size was also comparable with other compared Euphorbia species, as well as the Vernicia fordii chloroplast genome, which is 161,528 bp in length [32], suggesting that chloroplast genomes are conserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation